2017
DOI: 10.14709/barbj.10.1.2017.02
|View full text |Cite
|
Sign up to set email alerts
|

Conservación de colonias reproductoras de murciélagos cavernícolas mediante refugios artificiales.

Abstract: English title: Conservation of breeding colonies of cave-dwelling bats using man-made roosts. Conservación de colonias reproductoras de murciélagos cavernícolas mediante refugios artificialesResumen: Los murciélagos requieren refugios específicos donde establecer sus colonias reproductoras. Aunque generalmente utilizan refugios naturales, en muchas ocasiones también ocupan construcciones humanas siempre que mantengan determinadas condiciones ambientales y carezcan de molestias. En Acedo (Navarra, Norte de Espa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Additionally, because pups cannot readily thermoregulate early in development (Klug & Barclay, 2013;Noll, 1979;Sano, 2000;Studier & O'Farrell, 1972), pups could be more susceptible to high roost temperatures due to their inability to thermoregulate and lower thermal inertia (i.e., faster heating) compared to adults. For instance, Alcalde et al (2017) reported that artificial roost temperatures reached at least 36.6 C during a heatwave in northern Spain in July 2015, resulting in the death of five nonvolant Geoffroy's bat pups (Vespertilionidae: Myotis emarginatus) and temporary roost abandonment by adults.…”
Section: Thermal Tolerance Of Temperate Batsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, because pups cannot readily thermoregulate early in development (Klug & Barclay, 2013;Noll, 1979;Sano, 2000;Studier & O'Farrell, 1972), pups could be more susceptible to high roost temperatures due to their inability to thermoregulate and lower thermal inertia (i.e., faster heating) compared to adults. For instance, Alcalde et al (2017) reported that artificial roost temperatures reached at least 36.6 C during a heatwave in northern Spain in July 2015, resulting in the death of five nonvolant Geoffroy's bat pups (Vespertilionidae: Myotis emarginatus) and temporary roost abandonment by adults.…”
Section: Thermal Tolerance Of Temperate Batsmentioning
confidence: 99%
“…While instances of bat mortality at artificial roosts have been documented (Alcalde et al, 2017;Flaquer et al, 2014), these observations remain largely anecdotal and there is no comprehensive record. Poor documentation of mortality relating to bat box design and placement adds to the growing uncertainty surrounding bat box use.…”
Section: Increasing Popularity Uncertainty and Riskmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports of heatrelated mortality of pteropodid bats in the southern hemisphere, which are predicted to increase due to climate change (McKechnie et al, 2021;Ratnayake et al, 2019;Welbergen et al, 2008). Although less common, there are reports of heat-related mortality of vespertilionid bats using artificial roosts in South-Western Europe (Alcalde et al, 2017;Flaquer et al, 2014). These bats are also threatened by anthropogenic land-use changes, including deforestation, habitat fragmentation and plantation forests (Kunz & Parsons, 2009).…”
Section: Introductionmentioning
confidence: 99%